Applying a cognitive-emotional model to nonsuicidal self-injury - Dawkins, J.; Hasking, Penelope; Boyes, Mark; Greene, D.; Passchier, C. (John Wiley & Sons Ltd., 2018)
The recently proposed cognitive-emotional model of nonsuicidal self-injury (NSSI) draws on emotion regulation models and social cognitive theory to understand the onset, maintenance, and cessation of NSSI. We tested the prediction of the model that the relationship between emotional reactivity and NSSI is moderated by specific cognitions about self-injury (i.e., self-efficacy to resist NSSI, NSSI outcome expectancies), emotion regulation, and rumination. A sample of 647 university students aged 17–25 years (M = 19.92, SD = 1.78) completed self-report measures of the constructs of interest. As expected, we found that emotional reactivity was positively related to NSSI, particularly for people who had weak self-efficacy to resist NSSI. However, emotional reactivity was negatively related to NSSI for people who were more likely to use expressive suppression to regulate emotion. Implications for the theoretical understanding of NSSI are discussed.